2009
DOI: 10.1177/1721727x0900700204
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Pathological Autoimmunity following Mycobacterium Leprae Heat-Shock Protein 65-Dna Vaccination in Mice

Abstract: Heat-shock proteins (HSPs) are currently one of the most promising targets for the development of immunotherapy against tumours and autoimmune disorders. This protein family has the capacity to activate or modulate the function of different immune system cells. They induce the activation of monocytes, macrophages and dendritic cells, and contribute to cross-priming, an important mechanism of presentation of exogenous antigen in the context of MHe class I molecules. These various immunological properties of HSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
5
1
Order By: Relevance
“…Our results with mycobacterial Hsp administered as recombinant DNA indicate that the modulation of allergy can be achieved with reduced amounts of DNA. Despite the classical concerns about recombinant DNA in humans, our results and the results of other studies indicate that this type of formulation is safe for humans, does not integrate in the genomic DNA and does not induce autoimmune manifestations [37,38]. In addition, we showed that the suppressive effect conferred by DNA could be enhanced by an additional injection of r-Hsp65 protein into the airway.…”
Section: Discussionmentioning
confidence: 46%
“…Our results with mycobacterial Hsp administered as recombinant DNA indicate that the modulation of allergy can be achieved with reduced amounts of DNA. Despite the classical concerns about recombinant DNA in humans, our results and the results of other studies indicate that this type of formulation is safe for humans, does not integrate in the genomic DNA and does not induce autoimmune manifestations [37,38]. In addition, we showed that the suppressive effect conferred by DNA could be enhanced by an additional injection of r-Hsp65 protein into the airway.…”
Section: Discussionmentioning
confidence: 46%
“…As the infection progresses, the inflammatory response becomes mast-cell-and T cell-dependent. Moreover, in T. spiralis infection a wide range of inflammatory cytokines such as IL-I, IL-4, IL-6, IL-8, IFN-y and TNF-a and chemokines are produced (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Nakano and colI. (3) analyzed extirpated heart valves to detect cariogenic Streptococcus mutans, the only study in which aortic valves were analyzed to detect oral microorganisms (4)(5). However, the only bacteria which was detected in the analysis of the extirpated heart valves was S. Mutans.…”
mentioning
confidence: 99%